2008
DOI: 10.1007/s11085-008-9108-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Permeability of Nickel and Ni–Cu Alloys

Abstract: A Ni-20Cr alloy and variants containing 5, 10 and 20Cu (all in wt.%) were carburised in H 2 -5% CH 4 at 1,000°C. All alloys formed internal carburisation zones containing Cr 3 C 2 and Cr 7 C 3 . The Ni-20Cr alloy also developed a surface deposit of graphite, but the copper-bearing alloys did not. Measured parabolic rate constants for intragranular carburisation were used to calculate carbon permeabilities from Wagner's diffusion analysis. The value obtained for Ni-20Cr was in good agreement with the product of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Alloys of Ni20Cr, with and without copper additions, were found [26] to carburise at the same rate. It is therefore concluded that copper does not affect carbon permeability (N ðsÞ C D g C ), but does inhibit graphite nucleation.…”
Section: Effect Of Copper On Nickel and Stainless Steel Dustingmentioning
confidence: 87%
“…Alloys of Ni20Cr, with and without copper additions, were found [26] to carburise at the same rate. It is therefore concluded that copper does not affect carbon permeability (N ðsÞ C D g C ), but does inhibit graphite nucleation.…”
Section: Effect Of Copper On Nickel and Stainless Steel Dustingmentioning
confidence: 87%
“…On the other hand, point defects such as vacancies could be easily introduced during nucleation, radiation and corrosion processes, and defects in alloy always serve as the trapping site for carbon. The metal solute as well as defects and their interactions can greatly affect the carbon solubility, [13][14][15][16] diffusion, 15,16 carbon segregation 14 and carbide precipitations properties 14,17 in nickel. However, it is extremely difficult to directly observe the behavior of carbon and the corresponding microcosmic mechanisms since all of the FIAs-FSAs interactions are atomic-scale problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the 20 wt% Cu alloys, Cu rich phases developed causing internal carburization at the Cu-c phase interphases [44]. Recently, Zhang and Young [52] confirmed that Cu does not affect the C permeability in Ni as it was earlier proposed [53] but rather interferes with the nucleation of graphite.…”
Section: Cumentioning
confidence: 85%